Malaria among the Sauria Paharia, a primitive and vulnerable tribe of Jharkhand state, India - M Rajesh Kumar Rao; Manoj Kumar Das (Elsevier, 2021)
Background: Pakur district of Jharkhand state is highly malaria-endemic areas in eastern India, mainly inhabited by Sauria Paharia, a primitive and vulnerable tribal group. Methods: An epidemiological, entomological and malaria-related community-based education; and evaluation of the operational strategies for malaria interventions were performed in eight vulnerable forests-fringed tribal villages in the Pakur district of Jharkhand, India. Results: Of the 217 confirmed malaria infections, P. falciparum (92.2%), P. vivax (7.8%), and mixed-species infections (6.9%) were found. The SPR, SFR and Pf% ranged from 23.8 to 68.2, 23.8-64.8 and 84.2-100.0, respectively. An. culicifacies, An. annularis, An. fluviatilis and An. minimus became the primary vectors of malaria. Insecticidal susceptibility status indicates An. culicifacies and An. annularis resistance to DDT (4%); and An. culicifacies, An. annularis and An. fluviatilis susceptible to malathion (5%) and deltamethrin (0.05%). Most residents, including health staff, had excellent knowledge of malaria but did not adopt appropriate prevention steps. Many accredited social health activist workers have not trained to diagnose and treat malaria cases, nor have rapid diagnostic test kits and antimalarial drugs been available, resulting in the tribal community adopting traditional treatments and native remedies. Conclusion: High vector abundance, presence of parasite load, deficiency of prevention practices; and lack of early detection and prompt treatment and vector control strategies indicate that the population living in these provinces is more vulnerable to malaria. Therefore, periodic surveillance, monitoring, and evaluation are also needed to enhance the implementation of malaria interventions in this region.